Assessment of Antithrombotic Properties of Sodium Ibuprofen - Esquivel, Carlos O; Bergqvist, David; Björck, Claes-Göran; Carson, Stan N; Nilsson, Bodil (Thrombosis and Haemostasis, 1982)
The effect of sodium ibuprofen on platelet activity in vivo and the lysability of ex vivo thrombi was investigated. The formation of a hemostatic platelet plug in the rabbit mesentery and platelet embolism as a response to a laser-induced injury in the ear chamber of rabbits were used as models for determining platelet activity. Ibuprofen at a dose of 25 mg/kg i.v. was found to increase the primary (PHT) and the total hemostatic plug formation time (THT). The same dose decreased the number of cumulative emboli over a 10 min period after a laser injury to arterioles. A dose of 10 mg/kg i.v. did not affect the formation of the hemostatic platelet plug. In dogs, doses of 10, 25 und 50 mg/kg did not enhance the release of 125I-FDP from the thrombi after incubation in plasmin, but the largest dose which is approximately five times the recommended dose in humans, did significantly decrease the thrombus weight 90 and 180 min after the drug administration. In conclusion, sodium ibuprofen was shown to have an inhibitory effect on platelet function in vivo and in large doses was also found to diminish the thrombus weight.
Keywords: Ibuprofen; Platelets; Hemostasis; Fibrinolysis